Pengaruh Financial Literacy dan Financial Technology terhadap Kinerja UMKM (Studi Kasus Pada UMKM Sektor Kuliner Pengguna Aplikasi Grab Duri Bengkalis) - Simorangkir, Marini Rosalyn; Ruzikna, Ruzikna (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the influence of financial literacy and financial technology on the performance of SMEs: A Case Study on Culinary SMEs Using the Grab Application in Duri Bengkalis. The method used in this research is quantitative descriptive analysis using the SPSS Statistics 25 program. This study uses a population of 246 SMEs in the Culinary Sector of Duri Bengkalis that use the Grab Application. The sampling technique uses purposive sampling method with a sample size of 71 SME actors. The analysis methods used in this study are validity test, reliability test, normality test, multicollinearity test, heteroskedasticity test, simple regression analysis, multiple regression analysis, t-test, F-test, and coefficient of determination test. The results of this study indicate that (1) financial literacy has a positive and significant effect on SME performance, (2) financial technology has a positive and significant effect on SME performance, and (3) financial literacy and financial technology has a positive and significant effect on SME performance. Keywords: Financial Literacy, Financial Technology, MSME Performance, Duri Bengkalis Grab Application.